Comparison of Efficacy and Tolerability of Ferrous Sulfate and Carbonyl Iron in Iron Deficiency Anemia in Pregnant Woman - Ahmed, Taslima Nasreen; Shahriar, Iram; Md Iqbal, Jalal Uddin; Rowshan, Mahfuza Mazeda; Yusuf, Riti (Sir Salimullah Medical College Journal, 2022)
Introduction: Iron deficiency anemia in pregnancy is common and causes a huge burden globally. Bangladesh is known to have a high prevalence of iron deficiency anemia in pregnant women. Hence, it is important to evaluate the efficacy and tolerability of drugs in treatment of iron deficiency anemia in pregnancy. Objective: The purpose of present study was to compare the efficacy and tolerability of Ferrous Sulfate and Carbonyl Iron in Iron Deficiency Anemia in pregnant women. Methodology: An observational prospective study was conducted in obstetric and gynae out – patient department of Sir Salimullah Medical College and Mitford Hospital. Woman between 16 – 28 weeks of pregnancy with haemoglobin level 7 – 10 g/dl with microcytic hypochromic blood film were included in this study. Pregnant women in 1st and 3rd trimester of pregnancy were excluded from the study. Among the study population one group was given Tablet Ferrous Sulfate and another group was given Capsule Carbonyl Iron. Results: There was significant and comparable rise in HB in 4th, 8th and 12th week in the two group. (p<0.001). Carbonyl iron showed significantly more rise in Hb as compared to Ferrous Sulfate. Adverse effects were seen more in number and intensity with Ferrous Sulfate. Individual efficacy of both compounds was good but Carbonyl Iron was better tolerated. Conclusion: Carbonyl Iron is more effective and tolerable than Ferrous Sulfate in treatment of iron deficiency anemia in pregnancy. Sir Salimullah Med Coll J 2022; 30: 83-88